SYSTEMATIZE THE VOCABULARY OF FIRST-GRADERS IN THEIR NATIVE LANGUAGE - Nasirdinova Oydinniso Dagarovna (Scholar Express Journal, 2022)
In order to develop the vocabulary of first-graders in mother tongue education, the study of their speech, the identification of active and inactive words according to their age, and the systematic systematization of vocabulary, which must be mastered, ensure the effectiveness of quality in this area. and forms the basis for the gradual development of dictionaries from junior to senior.
Keywords: First-Class Dictionary Richness; Systematization Of Words; Systematic Dictionary; Macrosystem